Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

Đề sai e nhé
\(E=x^2\left(x+1\right)-y^2\left(y-1\right)+xy-3xy\left(x-y+1\right)+2017\)
\(=x^3+x^2-y^3+y^2+xy-3x^2y+3xy^2-3xy+2017\)
\(=\left(x^3-3x^2y+3xy^2-y^3\right)+\left(x^2-2xy+y^2\right)+2017\)
\(=\left(x-y\right)^3+\left(x-y\right)^2+2017\)
\(=\left(-3\right)^3+\left(-3\right)^2+2017\)
\(=-27+9+2017\)
\(=1999\)

a: \(=\dfrac{1}{x-y}-\dfrac{3xy}{\left(x-y\right)\left(x^2+xy+y^2\right)}+\dfrac{x-y}{x^2+xy+y^2}\)
\(=\dfrac{x^2+xy+y^2-3xy+x^2-2xy+y^2}{\left(x-y\right)\left(x^2+xy+y^2\right)}\)
\(=\dfrac{2x^2-4xy+2y^2}{\left(x-y\right)\left(x^2+xy+y^2\right)}=\dfrac{2\left(x-y\right)}{x^2+xy+y^2}\)
d: \(=\dfrac{x^3-1}{x-1}-\dfrac{x^2-1}{x+1}\)
\(=x^2+x+1-x+1=x^2+2\)
a) \(A=xy-3xy\left(1+x-y\right)+x^2\left(x+1\right)-y^2\left(y-1\right)\)
\(A=xy-3xy-3x^2y+3xy^2+x^3+x^2-y^3+y^2\)
\(A=x^2-2xy+y^2+x^3-3x^2y+3xy^2-y^3\)
\(A=\left(x-y\right)^2+\left(x-y\right)^3\)
b) Khi x-y =5
<=> x= 5+y
Thay vào bt A ,ta được:
\(A=\left(5+y-y\right)^2+\left(5+y-y\right)^3\)
\(A=5^2+5^3=25+125=150\)
\(A=xy-3xy\left(1+x-y\right)+x^2\left(x+1\right)-y^2\left(y-1\right)\)
\(A=xy-3xy-3x^2y+3xy^2+x^3+x^2-y^3+y^2\)
\(A=\left(x-y\right)^3+\left(x-y\right)^2\)
\(A=\left(x-y\right)^2\left(x-y+1\right)\)
b) Với x - y = 5 ta có
\(A=5^2.6=150\)